Ethnoconstructivism-Based E-module: Design, Implementation, and Contextualization of Local Wisdom-Based Procedural Text Learning in Elementary Schools - Afifah, Arista Nufus; Sukasih, Sri (FKIP Universitas Lampung, 2025)
Ethnoconstructivism E-module: Design, Implementation, and Contextualization of Local Wisdom-Based Procedural Text Learning in Elementary Schools. Objectives: Limited learning resources, low learning outcomes, and skills in writing procedural texts are among the problems at SDN 04 Randublatung. This research aims to develop, test the feasibility, and evaluate the effectiveness of an ethnoconstructivism-based e-module using Flip PDF Professional, integrated with the local wisdom of Blora, in improving learning outcomes, procedural text writing skills, and their contextualization in digital era learning. Method: This research uses the research and development (R&D) method with the ADDIE development design. Data collection was conducted using test (pretest and a posttest) and non-test techniques (observation, interviews, questionnaires, and documentation). Finding: The results of this study indicate that the e-modules developed are very feasible to use with a percentage of 92,6% (material experts) and 92% (media experts). The reliability of the multiple-choice questions is 0.87 and the reliability of the essay questions is 0.756, both are declared reliable. The normality test showed a sig > 0,05, indicating normal data distribution. The t-test result showed sig. 0,000 confirms an increase in learning outcome after using e-module. The effectiveness showed with n-Gain of 61,25% (learning outcomes) and 59.07% (writing skills), both in the moderately effective category. Local wisdom, the traditional coconut milk coffee of Blora, is used as a context to explain procedural text material, making it easier for students to relate to new knowledge. Conclusion: With the increase in the average, the learning material in the form of a professional flip PDF-based ethnoconstructivism e-module integrated with local Blora wisdom on procedural text material is effectively used in the fourth grade of elementary school. Keywords: e-module, Ethnokonstructivism, local wisdom, text procedures.